Cuidado entre a política e o direito: a construção do direito ao cuidado na agenda jurídico-política da América Latina - Leandra Cristina de Oliveira Costa (2024)
The present work aims to investigate care from the legal-political perspective of a right that must be offered to all people so that they have the right to care, to be cared for and to self-care. The agenda of demanding a right to care has been debated and implemented by several countries based on theoretical discussions in the field of care studies. The theme has expanded significantly in Latin America in recent years, especially after the Economic Commission for Latin America and the Caribbean (ECLAC) established and implemented the Regional Conference on Women in Latin America and the Caribbean as a subsidiary body of the commission, which in a period no longer than three years is convened to analyze and discuss the regional condition in relation to women's rights and autonomy. Over the years, countries participating in the conference have signed agreements aimed at implementing public policies and social measures in their countries to improve women's living conditions. From the Tenth Regional Conference on Women, held in Quito, Ecuador, in 2007, care was included in the discussion in which countries agreed that the social and economic value of women's unpaid domestic work and care should be recognized. should be treated as a public matter. In this sense, from this conference onwards, care began to be discussed in subsequent meetings and was taken up for internal discussion in some countries that implemented public care policies and recognized it as a right. From this scenario we begin our discussion towards thinking about care as a right to be established in the legal-political agenda of Latin America and as a way of promoting greater autonomy, equity and social justice for female figures. To this end, our discussions focus on the field of law, the development of public policies and the participation of the feminist movement in this process.